A Conversation with Dr. Mark Solms. Issue 1 (2nd January 2018) - Choder-Goldman, Jill
Abstract : In Global Perspectives, we bring you interviews with psychoanalysts from around the world in an effort to explore the influence of culture, politics, and socioeconomic issues and how they influence training, theory development, and adherence to clinical technique and psychoanalytic practice in general.